Escape from homeostasis: spinal microcircuits and progression of amyotrophic lateral sclerosis - Brownstone, Robert M.; Lancelin, Camille (Journal of neurophysiology, 2018)
In amyotrophic lateral sclerosis (ALS), loss of motoneuron function leads to weakness and, ultimately, respiratory failure and death. Regardless of the initial pathogenic factors, motoneuron loss follows a specific pattern: the largest α-motoneurons die before smaller α-motoneurons, and γ-motoneurons are spared. In this article, we examine how homeostatic responses to this orderly progression could lead to local microcircuit dysfunction that in turn propagates motoneuron dysfunction and death. We first review motoneuron diversity and the principle of α-γ coactivation and then discuss two specific spinal motoneuron microcircuits: those involving proprioceptive afferents and those involving Renshaw cells. Next, we propose that the overall homeostatic response of the nervous system is aimed at maintaining force output. Thus motoneuron degeneration would lead to an increase in inputs to motoneurons, and, because of the pattern of neuronal degeneration, would result in an imbalance in local microcircuit activity that would overwhelm initial homeostatic responses. We suggest that this activity would ultimately lead to excitotoxicity of motoneurons, which would hasten the progression of disease. Finally, we propose that should this be the case, new therapies targeted toward microcircuit dysfunction could slow the course of ALS.